Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1756284818758929
|View full text |Cite
|
Sign up to set email alerts
|

Video capsule endoscopy in pediatric patients with Crohn’s disease: a single-center experience of 180 procedures

Abstract: BackgroundVideo capsule endoscopy (VCE) is a noninvasive method enabling excellent visualization of the small bowel (SB) mucosa. The aim of this study was to examine the impact and safety of VCE performed in children and adolescents with suspected or established Crohn’s disease (CD).MethodsA total of 180 VCE examinations in 169 consecutive patients conducted in 2003–14 in a single center were retrospectively analyzed. The median age was 13 years (range 3–17 years) and indications for VCE were suspected (125 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Case reports have demonstrated that VCE is safe to use in children as young as 8 months or weighing as little as 7.9 kg. [ 11 , 12 ] The usefulness of VCE in children has been established for several small-bowel pathologies, such as Crohn's disease, [ 13 ] obscure gastrointestinal bleeding, [ 14 ] hereditary polyposis, [ 15 ] abdominal pain, and protein-losing enteropathy. [ 4 , 16 ] Furthermore, VCE is well suited for longitudinal monitoring of Crohn's disease activity in the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have demonstrated that VCE is safe to use in children as young as 8 months or weighing as little as 7.9 kg. [ 11 , 12 ] The usefulness of VCE in children has been established for several small-bowel pathologies, such as Crohn's disease, [ 13 ] obscure gastrointestinal bleeding, [ 14 ] hereditary polyposis, [ 15 ] abdominal pain, and protein-losing enteropathy. [ 4 , 16 ] Furthermore, VCE is well suited for longitudinal monitoring of Crohn's disease activity in the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Video capsule endoscopy (VCE) can detect mucosal lesions in the small bowel and is useful in evaluating small bowel involvement in suspected CD 53–55 . Its use has also resulted in a change in diagnosis from previously diagnosed UC to CD 53 or reclassification of the phenotype in confirmed CD cases 60 .…”
Section: Disease Monitoringmentioning
confidence: 99%
“…can detect mucosal lesions in the small bowel and is useful in evaluating small bowel involvement in suspected CD. [53][54][55] Its use has also resulted in a change in diagnosis from previously diagnosed UC to CD 53 or reclassification of the phenotype in confirmed CD cases. 60 However, the role of VCE in monitoring disease activity in small bowel CD has not been fully established.…”
Section: Video Capsule Endoscopy Video Capsule Endoscopy (Vce)mentioning
confidence: 99%